OPTIMASI TEMPERATUR DAN WAKTU PENGERINGAN MI KERING YANG BERBAHAN BAKU TEPUNG JAGUNG DAN TEPUNG TERIGU - Supraptiah, Endang (KINETIKA, 2019)
Dried noodles is one of favorite food in Indonesia because it’s simple and easy to cook. The use of corn flour as substitute for making noodles is an effort to diversify food in reducing the import of wheat flour. The objective of this study was to determine the optimum drying conditions to obtain the best quallity of dried noodles, with ratio composition of corn flour and wheat flour 2:3. This study used completely randomized design with temperature and time drying. Drying was conducted using a tray dryer at various temperature (60, 70, and 80oC) and various time drying (60, 70, 80 and 90 minutes). The observed quality parameters were water content, ash content and protein content. The result showed that the optimum drying condition is 80oC and 90 minutes long with water content 6,87%, ash content 1,78%, and protein content 19,39% and the result of the coefisient of drying rate (k) is 0,1218